TGF-β1 and TGF-β2 abundance in liver diseases of mice and men - Dropmann, Anne; Dediulia, Tatjana; Breitkopf-Heinlein, Katja; Dooley, Steven; Meindl-Beinker, Nadja M. (OncoTarget, 2016)
TGF-β1 is a major player in chronic liver diseases promoting fibrogenesis and tumorigenesis through various mechanisms. The expression and function of TGF-β2 have not been investigated thoroughly in liver disease to date. In this paper, we provide evidence that TGF-β2 expression correlates with fibrogenesis and liver cancer development. Using quantitative realtime PCR and ELISA, we show that TGF-β2 mRNA expression and secretion increased in murine HSCs and hepatocytes over time in culture and were found in the human-derived HSC cell line LX-2. TGF-β2 stimulation of the LX-2 cells led to upregulation of the TGF-β receptors 1, 2, and 3, whereas TGF-β1 treatment did not alter or decrease their expression. In liver regeneration and fibrosis upon CCl4 challenge, the transient increase of TGF-β2 expression was accompanied by TGF-β1 and collagen expression. In bile duct ligation-induced fibrosis, TGF-β2 upregulation correlated with fibrotic markers and was more prominent than TGF-β1 expression. Accordingly, MDR2-KO mice showed significant TGF-β2 upregulation within 3 to 15 months but minor TGF-β1 expression changes. In 5 of 8 hepatocellular carcinoma (HCC)/hepatoblastoma cell lines, relatively high TGF-β2 expression and secretion were observed, with some cell lines even secreting more TGF-β2 than TGF-β1. TGF-β2 was also upregulated in tumors of TGFα/cMyc and DEN-treated mice. The analysis of publically available microarray data of 13 human HCC collectives revealed considerable upregulation of TGF-β2 as compared to normal liver. Our study demonstrates upregulation of TGF-β2 in liver disease and suggests TGF-β2 as a promising therapeutic target for tackling fibrosis and HCC.
Gesehen am 02.04.2019